High Pressure Carbon Dioxide pasteurization of coconut water: A sport drink with high nutritional and sensory quality. (January 2015) - Cappelletti, Martina; Ferrentino, Giovanna; Endrizzi, Isabella; Aprea, Eugenio; Betta, Emanuela; Corollaro, Maria Laura; Charles, Mathilde; Gasperi, Flavia; Spilimbergo, Sara
Highlights: HPCD treatment guarantees the inactivation of natural microbial flora of coconut water. HPCD preserves better than thermal processing the nutritional and sensory qualities of coconut water. HPCD can contribute to commercialize coconut water as a highly natural energy-drink. Abstract: High Pressure Carbon Dioxide (HPCD) treatment was applied to the pasteurization of coconut water in order to guarantee both its microbial stability and preserve its nutritional and sensory attributes. It was demonstrated that 120 bar, 40 °C, 30 min were the optimal process conditions to induce a 5 Log(CFU/ml) reduction of mesophilic microorganisms, lactic acid bacteria, yeasts and molds and a 7 Log reduction of the total coliforms. The effect of HPCD on the quality traits of coconut water were investigated by means of physical–chemical and sensory analyses and compared to the Heat Pasteurized (HP, 90 °C, 1 min) and Fresh Untreated (FU) product. No differences in the basic chemical composition, vitamins and amino acids, were detected between HPCD and FU products. However, differences in the volatile compounds present in the three products were clearly distinguishable; HPCD resulted in a reduction of most of the volatile fractions while HP induced the formation of compounds with a toasted and malty aroma. Nevertheless, few sensory differences were perceived between the FU and the HPCD coconut water, and both were clearly differentiated from the HP product.